A quantitative study on the diffusion of public policy in China: evidence from the S&T finance sector. Issue 3 (3rd July 2017) - Huang, Cui; Yue, Xiaoxu; Yang, Mengqu; Su, Jun; Chen, Jing
Abstract: With the deepening of the reform and opening-up process, the National Development and Reform Commission, the Ministry of Science and Technology, the Ministry of Finance, and other relevant ministries in China have jointly promulgated thousands of policies and regulations in the last few decades. The objective has been to adjust science and technology (S&T) finance policy tools, and to continually optimize an environment of financial support for S&T innovation and related public policies. Studying the diffusion mechanisms of the S&T finance activities in the policy documents jointly issued by these ministries cannot only reflect the intersection and linkages between S&T activities and finance and taxation affairs, but can also create a scientific and feasible research path for the 'black box' that is the S&T finance policy process. Based on a review of policy diffusion theory and related literature, and taking China's S&T finance policy as the research subject, 367 central government policies and 3869 local government policies issued between 1981 and 2015 were collected using the Tsinghua University Government Documents Information System (GDIS). By analyzing the external attributes of the policy literature network, and the timing of keywords used by the internal tools of the policy literature, the process and characteristics of the policy diffusion of S&T achievements transformation were observed along the four dimensions of intensity, breadth, speed, and direction.